Should we take the gig economy seriously?. (3rd July 2017) - Healy, Joshua; Nicholson, Daniel; Pekarek, Andreas
ABSTRACT: The 'gig economy' has emerged rapidly as a form of service delivery that challenges existing business models, labour-management practices, and regulations. The ways in which platform companies transact with workers, in particular, has created a burgeoning public interest, but has yet to give rise to a corresponding academic literature. In this paper, we ask whether the gig economy deserves to be a subject of employment relations scholarship, given its current dimensions and likely future. We argue that academic analysis is needed, to better understand the power dynamics operating within the gig economy and how these are testing existing norms and institutions. We discuss two mains ways that employment relations researchers can expand their theoretical repertoires and, in doing so, improve the evidence on gig-based working arrangements. We begin to sketch the outlines of a systematic research agenda, by elaborating indicative questions that need addressing to advance understanding of 'gig work relations'. We caution, however, that academic analysis of the gig economy should not be predicated on an expectation that it is the future of work. A number of economic, industrial and political factors threaten to slow or halt the gig economy's growth.